Manganese 3×3 and 3√×3√-R30∘ structures and structural phase transition on w-GaN(0001¯) studied by scanning tunneling microscopy and first-principles theory - Chinchore, Abhijit V. (2013)
Manganese deposited on the N-polar face of wurtzite gallium nitride [GaN (0001¯)] results in two unique surface reconstructions, depending on the deposition temperature. At lower temperature (less than 105∘C), it is found that a metastable 3×3 structure forms. Mild annealing of this Mn 3×3 structure leads to an irreversible phase transition to a different, much more stable 3√×3√−R30∘ structure which can withstand high-temperature annealing. Scanning tunneling microscopy (STM) and reflection high-energy electron diffraction data are compared with results from first-principles theoretical calculations. Theory finds a lowest-energy model for the 3×3 structure consisting of Mn trimers bonded to the Ga adlayer atoms but not with N atoms. The lowest-energy model for the more stable 3√×3√−R30∘ structure involves Mn atoms substituting for Ga within the Ga adlayer and thus bonding with N atoms. Tersoff-Hamman simulations of the resulting lowest-energy structural models are found to be in very good agreement with the experimental STM images.